2008
DOI: 10.2214/ajr.07.3468
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Non-Imaging-Guided Glenohumeral Joint Injection Through Rotator Interval Approach in Patients Undergoing Diagnostic MR Arthrography

Abstract: The relative ease, efficiency, reproducibility, and accuracy of this method of non-imaging-guided anterior glenohumeral injection make it the method of choice at our institution, and we believe this technique merits consideration for more widespread utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 12 publications
2
25
0
1
Order By: Relevance
“…The 3D volume rendering reconstruction image (d) shows contrast material extravasation through the synovium of the biceps (arrow) and a normal axillary recess (arrowhead) studies have reported the amount, frequency and effects on diagnostic quality of these extravasations [6,13]. Except for extravasation along the needle path, contrast material can leak into the extra-articular structures due to the presence of a spontaneous rupture of the joint capsule [7]. This complication can have various causes; the amount of diluted contrast material can exceed the joint volume [14], the joint capsule can lose flexibility and tend to rupture [15] or there can be pathology resulting in a decrease in the joint volume [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D volume rendering reconstruction image (d) shows contrast material extravasation through the synovium of the biceps (arrow) and a normal axillary recess (arrowhead) studies have reported the amount, frequency and effects on diagnostic quality of these extravasations [6,13]. Except for extravasation along the needle path, contrast material can leak into the extra-articular structures due to the presence of a spontaneous rupture of the joint capsule [7]. This complication can have various causes; the amount of diluted contrast material can exceed the joint volume [14], the joint capsule can lose flexibility and tend to rupture [15] or there can be pathology resulting in a decrease in the joint volume [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, the shoulder joint capsule has some anatomical weak points. Excessive contrast material injection or increased injection pressure can result in tears in these anatomical weak points and thus extra-articular extravasation of the contrast material occurs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative anterior injection ) also show the imbibition superior one third of the SCT (arrow). One reader interpreted that there was a tear, whereas the other reader regarded it just a frayed tendon approach through the rotator interval has been used by several authors [8,11,34]. With this technique, which targets the medial upper third of the humeral head just lateral to the joint space, penetration of SCT can be avoided [8].…”
Section: Discussionmentioning
confidence: 99%
“…Favorable results have been reported in both anterior and posterior approach of glenohumeral joint injection without guidance of imaging device. 9,17) However, development Group 1: computer-generated blocked-randomization to receive either a blind glenohumeral injection of 40 mg triamcinolone, Group 2: ultrasound-guided injection of 40 mg triamcinolone. of imaging-guided injection technique, such as fluoroscopy or ultrasonography, was recommended for more accurate intraarticular injection.…”
Section: Discussionmentioning
confidence: 99%
“…Rutten et al 8) reported that US-guided glenohumeral joint injection is significantly less time consuming, causes less discomfort to the patient, and obviates the need for radiation and iodine contrast compared with fluoroscopicguided injection. On the other hand, Porat et al 9) reported that the accuracy of non-imaging-guided glenohumeral joint injection through the rotator interval is up to 99% on retrospective review of the post-injection magnetic resonance imaging (MRI) sequences. According to Patel et al, 10) although USguided injection could potentially reduce unnecessary attempts at glenohumeral placement, it has a disadvantage of being more time-consuming when compared with freehand injection.…”
Section: Introductionmentioning
confidence: 99%